Synergistic effect of glycine and triethanolamine on mechanical properties and permeability of cement mortar. (1st July 2022) - Jiang, Junyi; Liu, Baoju; Shi, Jinyan; Gencel, Osman; An, Xiang; Gao, Jiafeng
Abstract: Deeply understanding the synergistic effect and mechanism of different kinds of ionic complexing agents in cement-based materials is necessary. This paper aimed at investigating the synergistic effect of glycine and triethanolamine (TEA) on the mechanical properties, permeability and microstructure of mortars, and the synergistic mechanisms behind this effect were explored. The results demonstrate that incorporating 1–1.5% glycine alone can improve the mechanical properties of the mortar, which is related to sufficient glycine promoting the hydration of C3 A on the basis of transporting multiple metal ions. When the glycine content is 1%, although incorporating a small amount of TEA can further improve the performance of the mortar, the mortar with 0.04% TEA and 1% glycine shows the optimum mechanical properties and impermeability. Both glycine and TEA act as ionic complexing agents, their synergistic mechanism is also reflected in the difference of their complexing ions and complexing orders, and glycine can provide a suitable action environment for TEA. Therefore, the synergistic effect of glycine and TEA in cement hydration significantly improves the mechanical properties and permeability of mortar, which provides theoretical guidance for the application of ionic complexing agents in cement-based materials. Graphical abstract: Image 1 Highlights: The mechanical properties and transport properties of cement mortar are investigated. Glycine and triethanolamine have a significant synergistic effect on cement hydration. When the content of glycine and triethanolamine is 1% and 0.04%, the performance of the mortar is the best.